A numerical analysis of the effects of manufacturing processes on material pre-strain in offshore wind monopiles - Anandavijayan, Satya; Mehmanparast, Ali; Brennan, Feargal (Elsevier, 2018)
The majority of offshore wind turbines in Europe are supported by monopile type foundation structures. Monopiles are made of large thickness steel plates which are longitudinally welded to fabricate “cans” and these cans are subsequently welded around the circumference to manufacture a monopile. Monopile structures can have diameters of 4-10m, with wall thicknesses of 40-150mm. To achieve the cylindrical shape in individual cans, large thickness steel plates are typically cold formed via the three-roll bending process. During forming of these plates, the material is subjected to plastic pre-strain, which subsequently influences the fracture and fatigue properties of monopile structures. In this study, a finite element model has been developed to predict the pre-straining levels in monopiles of different dimensions. To determine the influence of numerous manufacturing practices, a sensitivity analysis of different factors has been conducted. These include fabrication dependent variables such as the influence of friction coefficient and bending force, and geometry dependent factors such as plate thickness, length, and distance between rollers. From the numerical results, a range of expected material pre-strain levels have been identified and presented in this paper.
Keywords: material pre-strain; monopile; fatigue; fracture; S355; finite element analysis; three roll bending